Green‐Light‐Activated Photoreaction via Genetic Hybridization of Far‐Red Fluorescent Protein and Silk. Issue 6 (12th March 2018) - Leem, Jung Woo; Park, Jongwoo; Kim, Seong‐Wan; Kim, Seong‐Ryul; Choi, Seung Ho; Choi, Kwang‐Ho; Kim, Young L.
Abstract: Fluorescent proteins often result in phototoxicity and cytotoxicity, in particular because some red fluorescent proteins produce and release reactive oxygen species (ROS). The photogeneration of ROS is considered as a detrimental side effect in cellular imaging or is proactively utilized for ablating cancerous tissue. As ancient textiles or biomaterials, silk produced by silkworms can directly be used as fabrics or be processed into materials and structures to host other functional nanomaterials. It is reported that transgenic fusion of far‐red fluorescent protein (mKate2) with silk provides a photosensitizer hybridization platform for photoinducible control of ROS. Taking advantage of green (visible) light activation, native and regenerated mKate2 silk can produce and release superoxide and singlet oxygen, in a comparable manner of visible light‐driven plasmonic photocatalysis. Thus, the genetic expression of mKate2 in silk offers immediately exploitable and scalable photocatalyst‐like biomaterials. It is further envisioned that mKate2 silk can potentially rule out hazardous concerns associated with foreign semiconductor photocatalytic nanomaterials. Abstract : Transgenic hybridization of far‐red fluorescent protein (mKate2) and silk provides a scalable and eco‐friendly photosensitizer platform that can be controlled by green (visible or solar) light. Native and regenerated mKate2 silk can generate superoxide and singlet oxygen in a comparable manner of visible‐light‐driven plasmonic photocatalysis. Thus, transgenic mKate2 silk is a plasmonic photocatalyst‐like biomaterial.